Liquid lipase‐catalyzed hydrolysis of gac oil for fatty acid production: Optimization using response surface methodology. (3rd October 2018) - Su, Chia‐Hung; Nguyen, Hoang Chinh; Nguyen, My Linh; Tran, Phung Thanh; Wang, Fu‐Ming; Guan, Yu‐Lin
Abstract : Fatty acids are valuable products because they have wide industrial applications in the manufacture of detergents, cosmetics, food, and various biomedical applications. In enzyme‐catalyzed hydrolysis, the use of immobilized lipase results in high production cost. To address this problem, Eversa Transform lipase, a new and low‐cost liquid lipase formulation, was used for the first time in oil hydrolysis with gac oil as a triglyceride source in this study. Response surface methodology was employed to optimize the reaction conditions and establish a reliable mathematical model for predicting hydrolysis yield. A maximal yield of 94.16% was obtained at a water‐to‐oil molar ratio of 12.79:1, reaction temperature of 38.9 °C, enzyme loading of 13.88%, and reaction time of 8.41 h. Under this optimal reaction condition, Eversa Transform lipase could be reused for up to eight cycles without significant loss in enzyme activity. This study indicates that the use of liquid Eversa Transform lipase in enzyme‐catalyzed oil hydrolysis could be a promising and cheap method of fatty acid production. © 2018 American Institute of Chemical Engineers Biotechnol. Prog., 2018